The Textual Structure of the Jessica-Mirna Judicial Text: An Forensic Linguistic Approach - Fitri, Nidya; rtawa, Ketut; Sri Satyawati, Made; Sawirman, - (e-Journal of Linguistics; Vol 13 No 1 (2019): e-jl-January, 2019)
This current study, in which the forensic linguistic approach and the theory of textual generic structure were applied, focuses on the judicial text in which Jessica was the defendant and Mirna was the victim. The judicial text, in which Jessica was the defendant and Mirna was the victim, is a dialogical conversation containing the textual procedure referring to structure. The textual structure of the judicial text, in which Jessica was the defendant and Mirna was the victim, is made up of three main phases; they are the textual structure of the opening, the textual structure of the content and the textual structure of the closing. Each phase is made up of sub-phases. The qualitative descriptive method was employed in the study. The data were collected through observation and recording, and were obtained from 17 audio-visual recordings, which were then transcribed into Indonesian. The findings of the study show that (1) the opening phase  was made up of the criminal trial phase, the interrogation phase of the defendant’s identity, the  indictment reading phase by the general prosecutor ; (2) the content phase was made up of the question phase as to  objection from the defendant (exception), the interrogation phase of the witnesses and expert, namely their (a) identities, (b) oath taking, and (c) the testimony of the witnesses and expert and the interrogation phase of the defendant; (3) the textual structure of the closing was made up of the indictment reading phase by the prosecutor, the verdict reading phase, and the trial closing phase. The finding of the study shows the representation of the textual structure as the textual procedural standard based on the judicial text used in the current study.